Sedentary behavior and health concepts, assessments, and interventions - Owen, Neville; Zhu, Weimo 1955- (Human Kinetics, 2017)
From office jobs and long commutes to passive entertainment like television and video games, humans are sitting more than ever. Though lack of exercise has major health consequences, researchers are now examining the additional and widespread health risk of the simple act of sitting for extended periods. With research from leading scientists, Sedentary Behavior and Health: Concepts, Assessments, and Interventions presents evidence on sedentary behavior, its apparent health risks, and suggestions on measuring and altering this behavior. The highly respected international author team provides an interdisciplinary review of current research, examining scientific, public health, and broader social questions about the implications of sedentary behavior. These topics include humans' physiological predispositions, exacerbation of current health conditions like obesity and diabetes, and the design and ergonomics of offices and chairs. To examine the many facets of this developing area of study, Sedentary Behavior and Health is divided into five parts: "Sedentary Behavior Concepts and Context" reviews the physiology of sedentary behavior, investigating current habits from the perspectives of evolution, industrial engineering, and design; "Sedentary Behavior and Health" explores the relationship between sedentary behavior and several major chronic diseases, including obesity, cardiovascular disease, and low-back pain; "Measuring and Analyzing Sedentary Behavior" explains research methods for understanding and measuring sedentary behavior in order to recognize patterns and design interventions; "Sedentary Behavior and Subpopulations" covers issues, risks, and behaviors in groups such as children, working adults, older adults, and minorities; "Changing Sedentary Behavior" provides methods and recommendations for improvement with environmental, social, community, worksite, and technology-based interventions. Included in this groundbreaking text are learning objectives, key concepts, and study questions to focus attention on key issues and reinforce concepts. Reviews of the literature in the field are presented, many with comparisons in table form, to provide the full scope of research. Sidebars throughout the text apply theoretical concepts to real-world scenarios. Inactivity is mismatched with many aspects of humans' genetic makeup. While it is becoming the new norm, the consequences of this behavior are emerging as a public health threat. Sedentary Behavior and Health will serve as a key reference for the rapidly emerging research area of sedentary behavior.